2001
DOI: 10.1055/s-2001-17864
|View full text |Cite
|
Sign up to set email alerts
|

Acute Budd-Chiari syndrome, portal and splenic vein thrombosis in a patient with ulcerative colitis associated with antiphospholipid antibodies and protein C deficiency

Abstract: We report the case of a female patient who had severe thrombotic complications in peripheral (V. jugularis, subclavia, brachialis, poplitea) and visceral (portal and splenic) veins 4 years after the first diagnosis of severe ulcerative pancolitis. A thrombolysis therapy for subclavian and jugular vein thrombosis was performed without complication, but she soon developed acute thrombosis of the hepatic veins (acute Budd-Chiari syndrome). She quickly recovered after liver transplantation and now - 6 years later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Apart from the 8/70 (11.4%) children with early TE recurrence within the same hospitalization, 12,15,18,30,36-38 7/ 70 (10%) experienced a separate TE recurrence, 17,18,20,28,29,40 with two presenting more than one recurrence. 29,40 The interval between the first and the second episode of TE ranged from 1 month to some years.…”
Section: Risk Of Recurrencementioning
confidence: 94%
See 2 more Smart Citations
“…Apart from the 8/70 (11.4%) children with early TE recurrence within the same hospitalization, 12,15,18,30,36-38 7/ 70 (10%) experienced a separate TE recurrence, 17,18,20,28,29,40 with two presenting more than one recurrence. 29,40 The interval between the first and the second episode of TE ranged from 1 month to some years.…”
Section: Risk Of Recurrencementioning
confidence: 94%
“…Of the 12 cases of abdominal TE, 11 were venous (five Budd-Chiari syndromes, [29][30][31][32]58 three portal veins, 22,29,33 two superior mesenteric vein, 33,34 one splenic vein 29 ) and one arterial (multiple colon vessels). 31 Abdominal thrombosis in children with IBD occurred significantly later in life compared to cerebral thrombosis (mean age 15.1 6 2.2 years for abdominal TE versus 11.7 6 4.8 years for cerebral TE, P ¼ 0.01).…”
Section: Abdominal Tementioning
confidence: 99%
See 1 more Smart Citation
“…One could speculate that this difference in efficacy would have been even greater with a larger sample size and with controlling for TE disease severity, as it is likely that CDT may have been reserved for patients with greater TE burden. 8,24,56 Regarding safety, both GI and non-GI HCs tended to be more common in the CDT group, although neither difference reached statistical significant. The lack of a significant difference may again be the result of small sample size, or it may reflect the relative safety of CDT, even in patients with IBD.…”
Section: Discussion Epidemiology and Pathogenesis Of Ibd-associated Tmentioning
confidence: 48%
“…However, several lines of evidence suggested that prompt cytoreduction is prudent. There are reports of unexpected thrombotic events in patients with reactive thrombocytosis [13][14][15]. Peritoneal inflammation and portal septic embolic thrombi causes portal vein thrombosis even in normal subjects [16].…”
Section: Discussionmentioning
confidence: 99%